Strategi Pengembangan Kerajinan Sentragabah dalam Meningkatkan Daya Tarik Wisata Edukasi di Desa Bumijaya, Kecamatan Ciruas, Kabupaten Serang - Saeful Fachri; Rani Dewi Yulyani; Sinta Agustina (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2025)
The pottery artisan community in Bumijaya Village faces several major challenges, such as the lack of modern marketing strategies, limited innovation in product design and functionality, and the suboptimal management of education-based tourism development. This study employs the Participatory Action Research (PAR) method, which emphasizes active community involvement in every stage of research and action. Observations indicate that Bumijaya Village has tourism potential that can be developed into an educational tourism attraction. Furthermore, based on observations and program implementation, there has been an increase in community awareness regarding the importance of innovation in pottery production and its utilization in the educational tourism industry.